Characterization of the Cellulose Fibers Extracted from the Bark of Piliostigma Racemosa. Issue 13 (1st December 2022) - Ramkumar, R.; Saravanan, P.
ABSTRACT: The purpose of this present investigation is to characterize the cellulosic fibers extracted from the bark of Piliostigma racemosa plant to assess the suitability of these fibers for reinforcing polymers. Characterization tests conducted are reported proving the reinforcing capability of these fibers. Chemical analysis shows the presence of cellulose (60.30 wt. %), lignin (30.76 wt. %), wax (0.63 wt. %), ash (1.12 wt. %) and wetness content (6.92 wt. %) with the fiber density of 1.371 g/cm 3 . Tensile strength, strain and Young's modulus of the fibers were 32MPa, 1.2–3.2% and 2GPa, respectively. Fourier Transform Infrared studies prove the presence of essential biopolymers and the X-ray diffraction studies purports the semi crystalline cellulose content with crystallinity index and the crystallite size calculated as 56.69% and 5.25 nm, respectively, and the mean micro-fibrillar angle of the fibers was found as 18.9°. The fibers are capable of sustaining a temperature of about 244°C as ascertained from the thermo-gravimetric analysis. The surface morphology claims that the fibers are rough and they can maintain a good interfacial adhesion with the matrix during composite fabrication. Thus, the fibers possess sufficient physico-chemical, thermal, and morphological features that enable them to be potential reinforcing agents in polymer composites.